Toxicity of palm oil to eggs and larvae of Callosobruchus maculatus (F.) on stored cowpea - Osekre, E.A.; Gbewonyo, W.S.K.; Ayertey, J.N. (Insect Science and its Application, 2002)
A commercially produced palm oil brand, Palmin oil, was evaluated for its effect on eggs and larvae of Callosobruchus maculatus (F.) (Coleoptera: Bruchidae) on cowpea (Vigna unguiculata (L.) Walp. Application of 1 μl of the oil on eggs deposited on 10 cowpea seeds, or directly on larvae growing inside seeds resulted in their death. Embryo mortality occurred only when the oil was placed at the anterior end of the egg. The nutritive content of cowpea seeds treated with Palmin oil remained unchanged. Furthermore, the oil did not go rancid following six months of storage. © 2002 ICIPE.
Keywords: Callosobruchus maculatus; Cowpea; Nutritional status; Palm oil; Storage